Leveraging Microalgae to Achieve Zero Hunger: Enhancing Livestock Feed for Nutritional Security - Leila Urrutia-Mazzuca; Marcia Mazzuca; María José Ibáñez-González; Tania Mazzuca-Sobczuk (Biomass)
Achieving “Zero Hunger” (SDG 2) requires overcoming complex challenges, especially in vulnerable communities in developing countries. Livestock plays a key role in food security, but limited resources threaten productivity, prompting interest in innovative solutions like microalgae supplementation in ruminant diets. Microalgae offer potential benefits by enhancing productivity and nutrition while addressing local protein deficiencies. However, barriers such as economic costs, processing requirements, and resistance to changing traditional feeding practices present challenges. This review examines the feasibility of microalgae-based livestock feed as a sustainable strategy to improve food security, particularly in arid, climate-affected regions. Biomass yield estimates suggest that small-scale cultivation can meet livestock nutritional needs; for example, a 22-goat herd would require approximately 88 g of microalgae per day to enrich meat with polyunsaturated fatty acids. Semi-continuous production systems could enable smallholders to cultivate adequate biomass, using local agricultural resources efficiently. This approach supports food security, improves meat quality, and strengthens community resilience. Collaboration among researchers, extension services, and local farmers is essential to ensure the effective adoption of microalgae feed systems, contributing to a sustainable future for livestock production in vulnerable regions.